Tradisi Merti Dusun, Kesadaran Adat, dan Dinamika Ekonomi Lokal: Praktik Keagamaan Masyarakatan Nahdlatul Ulama di Kelurahan Dukuh, Kota Salatiga - Lutfiani Dewi Fatmawati (Lakpesdam PCNU Kota Salatiga, 2024)
The Merti Dusun tradition in Dukuh Subdistrict (Kelurahan Dukuh), Salatiga City, is a religio-cultural practice that continues to persist amid modernization and shifting social orientations within the community. This tradition functions not only as an expression of gratitude and respect for ancestral heritage, but also as a space for integrating Nahdlatul Ulama’s distinctive religious practices (amaliyah) and for stimulating an event-based local economy. Against this backdrop, the study addresses two questions: (1) how is Merti Dusun constructed as an NU-oriented religio-cultural practice encompassing ritual, symbols, ritual time-space, and tahlil/pilgrimage that shapes meaning and community solidarity; and (2) how does Merti Dusun strengthen adat awareness and mobilize social capital and the local economy through participation, networks, collective contributions, and transactions in the context of modernization? The study employs a qualitative field-research design, using purposive interviews, documentation, and a literature review. Key informants include Head of RW 01, Dukuh Krajan and Zumrotun wife of the local modin), enabling the study to capture both community governance perspectives and religio-ritual dimensions. The findings show that Merti Dusun is held annually in the month of Safar through two main sequences: a ritual procession on Selasa Kliwon (communal village/cemetery cleaning, tahlil, collective prayers, and communal meals at the cemetery) and a cultural celebration on Minggu Kliwon (a cultural parade and traditional performances). The tradition reinforces solidarity and adat awareness through mutual cooperation, norms of reciprocity, and coordination across neighborhood units (RT/RW), while also generating an event-based local economy through routine community contributions, ritual donations (approximately IDR 6 million), and transaction flows during the cultural parade (approximately IDR 90 million). The study concludes that Merti Dusun constitutes a key nexus of culture, religion, economy, yet it faces risks of meaning erosion and commodification. The study recommends strengthening intergenerational transmission of values, improving event governance to safeguard authenticity and the sacred dimension, and developing local MSMEs in a targeted manner to enhance economic benefits without undermining the tradition’s religio-social significance.